Automated open-source software for charge transport analysis in single-carrier organic semiconductor diodes - Felekidis, Nikolaos; Melianas, Armantas; Kemerink, Martijn (Organic electronics, 2018)
Organic electronics is an emerging technology with numerous applications in which the active layer is composed of an organic semiconductor (OSC) or blends of multiple OSC. One of the key performance parameters for such devices is the charge carrier mobility which can be evaluated by different measurement techniques. Here, we review different formalisms for extraction and analysis of hole mobilities from temperature-dependent space-charge limited conductivity (SCLC) measurements for pristine OSC as well as for binary and ternary blends as used in e.g. photovoltaic applications. The model is also applicable to n-type materials. Possible sources of measurement errors, such as the presence of traps and series resistance, are discussed. We show that by a simple method of selecting a proper experimental data range these errors can be avoided. The Murgatroyd-Gill analytical model in combination with the Gaussian Disorder Model is used to extract zero-field hole mobilities as well as estimates of the Gaussian energetic disorder in the HOMO level from experimental data. The resulting mobilities are in excellent agreement with those found from more elaborate fits to a full drift-diffusion model that includes a temperature, field and density dependent charge carrier mobility; the same holds for the Gaussian disorder of pure materials and blends with low fullerene concentration. The zero-field mobilities are also analyzed according to an Arrhenius model that was previously argued to reveal a universal mobility law; for most -but not all- material systems in the present work this framework gave an equally good fit to the experimental data as the other models. An automated fitting freeware, incorporating the different models, is made openly available for download and minimizes error, user input and SCLC data analysis time; e.g. SCLC current-voltage curves at several different temperatures can be globally fitted in a few seconds.